URGENSI KEBIJAKAN REKRUTMEN APARATUR SIPIL NEGARA DALAM KOMPONEN CADANGAN - Fauzan Hidayat (Fakultas Politik Pemerintahan IPDN, 2022)
Abstract The purpose of this study is to determine the urgency and relevance of the state civil apparatus recruitment policy to become part of the reserve component of the indonesian national army. The involvement of the state civil apparatus in the reserve component is intended as a form of support for state defense and as evidence of the implementation of the core values of the state civil apparatus morals, namely loyalty to the nation and state so as to form the character of the state civil apparatus which is nationalist and statesman. In fact, in the recruitment process asn itself has referred to law number 5 of 2014 and government regulation number 17 of 2020 concerning the state civil apparatus management which has explicitly regulated the internalization of pancasila values, the 1945 constitution and the legitimate government and holds a code of ethics through oaths in accordance with their religious beliefs which ultimately forms the character of the nationalist and statesman of the state civil apparatus. The results showed that: 1) the state civil apparatus recruitment policy in the reserve component has urgency as a support for state defense, and to strengthen state defense run by the tni; 2) the state civil apparatus recruitment scheme in the reserve component has been comprehensively outlined in law 23 of 2019 on national resource management. But it has not referred to the principle of recruitment and the scale of priorities.; 3) the state civil apparatus recruitment policy in the reserve component is not yet relevant because the asn has been equipped with various state defense materials that are closely related to the element of loyalty -which is the main objective of the involvement of asns in the komcad- at the time of çivil servant candidate basic training, pre-service training, and leadership training. Keywords: The State Civil Apparatus, Defense, Reserve Components, Policy, Recruitment, Relevance